Interaction of 2,4-D or Dicamba with Glufosinate for Control of Glyphosate-Resistant Giant Ragweed (Ambrosia trifida L.) in Glufosinate-Resistant Maize (Zea mays L.) - Ganie, Zahoor A.; Jhala, Amit J. (Frontiers in Plant Science, 2017)
Glyphosate-resistant (GR) giant ragweed is a problematic broadleaf weed in crops including maize and soybean in the Midwestern United States. Commercialization of crops with 2,4-D or dicamba and glufosinate resistance will allow post-emergence (POST) applications of these herbicides. Therefore, information is needed on how 2,4-D/dicamba will interact with glufosinate in various rate combinations. The objectives of this study were to evaluate the interaction of glufosinate plus 2,4-D and/or dicamba for control of GR giant ragweed, and to determine their effect on GR giant ragweed density, biomass, maize injury, and yield. Field experiments were conducted in 2013 and 2014 in a field infested with GR giant ragweed in Nebraska, USA. The treatments included POST applications of glufosinate (450 or 590 g ai ha–1), 2,4-D, or dicamba at 280 or 560 g ae ha–1 applied alone and in tank-mixtures in glufosinate-resistant maize. The results showed that dicamba applied alone resulted in 56 to 62% and 73 to 83% control at 14 and 28 DAT, respectively, and ≥ 95% control at 60 days after treatment (DAT) or at harvest compared to 17 to 30% and 57 to 73% control with 2,4-D applied alone at 280 and 560 g ai ha–1, respectively. Glufosinate tank-mixed with 2,4-D and/ or dicamba consistently provided ≥ 90% control of GR giant ragweed, except that control with glufosinate plus 2,4-D varied from 80 to 92% at 60 DAT and at harvest. The comparison between the observed and expected control (determined by Colby’s equation) suggested an additive interaction between glufosinate and 2,4-D or dicamba for control of GR giant ragweed. Contrast analysis also indicated that GR giant ragweed control with glufosinate plus 2,4-D or dicamba was either consistently higher or comparable with individual herbicides excluding 2,4-D applied alone. Herbicide programs, excluding 2,4-D at 280 g ae ha–1, resulted in ≥ 80% reduction in GR giant ragweed density. Tank-mixing glufosinate with 2,4-D or dicamba showed an additive effect and will be an additional tool with two effective modes of action for the management of GR giant ragweed in maize.